Inertial reproduction: is the two-child psychology the rule in Costa Rica? - Rojas Blanco, Laura Cristina (2019)
This paper uses data from National Surveys on Sexual and Reproductive Health to test whether variables related to identity, sexuality and contraceptive knowledge are associated with the preference and demand for children in Costa Rica. Both the preferred and actual number of children are estimated with a double hurdle model. The findings indicate that preferences for children seem to be quite fixed around two children and are mainly associated with religious beliefs and the person’s gender, but they are not found to be associated with human capital. In contrast, the probability of having a child and the number of children are related to investment in human capital and sex education. Hence, human capital might be relevant in bringing a child into the world, but not in the initial preference.